2002
DOI: 10.1103/physrevb.65.094108
|View full text |Cite
|
Sign up to set email alerts
|

Strong hydrogen-related electronic effects on the shear elastic constant ofTaV2H(D)x

Abstract: Resonant ultrasound spectroscopy has been used to measure the shear modulus of the C15 Laves-phase compounds TaV 2 H(D) x . Polycrystalline samples with x(H)ϭ0. 00, 0.06, 0.10, 0.18, 0.34, and 0.53 and x(D)ϭ0.17 were investigated. Measurements were made over a temperature range of 3-345 K. Both the temperature dependence and the magnitude of the shear modulus ͓G(T)͔ were found to be highly dependent on the hydrogen concentration ͑x͒. At 20 K, G(T) for TaV 2 H 0.53 was 55% greater than that of TaV 2 . For H co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Figure 1 gives the polycrystalline shear modulus G ¼ C 44 of bcc Ta 0.33 V 0.67 as a function of temperature. Also shown for comparison are the results from the previous study of C15 TaV 2 [7]. Figure 2 gives the bulk modulus calculated from B ¼ C L À ð4=3ÞG (C L ¼ C 11 , polycrystalline).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Figure 1 gives the polycrystalline shear modulus G ¼ C 44 of bcc Ta 0.33 V 0.67 as a function of temperature. Also shown for comparison are the results from the previous study of C15 TaV 2 [7]. Figure 2 gives the bulk modulus calculated from B ¼ C L À ð4=3ÞG (C L ¼ C 11 , polycrystalline).…”
Section: Resultsmentioning
confidence: 96%
“…However, the thermal expansion coefficient of C15 TaV 2 was found to be positive [2]; thus, the unusual temperature behaviour is likely due to the second term of equation (1). A mechanism based on electronic structure was proposed to explain the unusual behaviour found in a number of C15 materials [1,[3][4][5][6][7]. The C15 crystal structure gives doubly-degenerate electronic levels at the X point of the Brillouin zone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall result, for typical materials, is that the elastic moduli approach 0 K with zero slope and decrease monotonically with increasing temperature. This simple picture is not applicable to materials undergoing phase transitions [22,23] or to materials with more complicated electronic structures [24][25][26]. Figs.…”
Section: Resultsmentioning
confidence: 96%
“…On the other hand, also other C15 Laves phases exhibit an anomalous softening, which has been related to the particular electronic properties of these compounds [11,12], and is influenced by the extra electrons supplied by H. Indeed, we observed that the increase of H concentration increases the temperature of the phase transformation and decreases the amplitude of the minimum in the modulus up to its disappearance in the ZrV 2 H 1 compound.…”
Section: Low Concentrations: Up To 25 Mol% Hmentioning
confidence: 84%